2022
DOI: 10.1002/vnl.21963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline treatment on physical, mechanical, and thermal characteristics of jute filler reinforced epoxy composites

Abstract: With burgeoning environmental concerns worldwide, using natural fibers/ fillers to produce composites rather than conventional fibers is on the rise. The current work focuses on the physical and thermomechanical characteristics of alkaline-treated jute filler-based epoxy composites. The composites have been prepared with different weight fraction of jute fillers (0%, 2.5%, 5%, 7.5%, 10%, and 12.5%) using hand layup process. The X-ray diffraction and Fourier transform infrared spectroscopy analysis observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 50 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…After that, the drastic fall of around 50% weight occurs in the second stage when the temperature remains between 380°C and 430°C due to the degradation of PEF/PGA blends. Final stage, the left‐over substances showed the weight to fall nearby 10%–14% up to the finishing temperature of 550°C due to the carbonization and phase transformation of the materials 34–36 . Furthermore, it was also noted that both the T d,5% and T d,max of the blends decreased after PGA was introduced into the PEF matrix, this is mainly due to the fact that the PGA molecular chain has numerous carbonyl groups, resulting in relatively poor thermal stability of PEF/PGA blends compared with neat PEF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the drastic fall of around 50% weight occurs in the second stage when the temperature remains between 380°C and 430°C due to the degradation of PEF/PGA blends. Final stage, the left‐over substances showed the weight to fall nearby 10%–14% up to the finishing temperature of 550°C due to the carbonization and phase transformation of the materials 34–36 . Furthermore, it was also noted that both the T d,5% and T d,max of the blends decreased after PGA was introduced into the PEF matrix, this is mainly due to the fact that the PGA molecular chain has numerous carbonyl groups, resulting in relatively poor thermal stability of PEF/PGA blends compared with neat PEF.…”
Section: Resultsmentioning
confidence: 99%
“…Final stage, the leftover substances showed the weight to fall nearby 10%-14% up to the finishing temperature of 550 C due to the carbonization and phase transformation of the materials. [34][35][36] Furthermore, it was also noted that both the T d,5% and T d,max of the blends decreased after PGA was introduced into the PEF matrix, this is mainly due to the fact that the PGA molecular chain has numerous carbonyl groups, resulting in relatively poor thermal stability of PEF/PGA blends compared with neat PEF. However, all the blends showed the T d,5% ranging from 310 C to 340 C and the T d,max ranging from 385 C to 410 C. Based on the above results, it indicated that those blends possess excellent thermal stability, and PEF/PGA blends can be processed safely without thermal degradation below 300 C.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Jute fibers are often utilized in flooring carpet, household, and industrial textile materials. [88][89][90][91][92][93][94] Hemp (Cannabis sativa L.) is a bast fiber that is collected from the stem of the plant. Europe and Asia are the predominant hemp-growing regions.…”
Section: Bast Fibersmentioning
confidence: 99%
“…The use of jute composites can replace wood. Jute fibers are often utilized in flooring carpet, household, and industrial textile materials 88–94 …”
Section: Natural Fibersmentioning
confidence: 99%
“…As example alkaline solution cannot be associated with phosphate-based treatment. Alkaline treatments based on alkali metal hydroxide are already used on naturals fibers [9,17] but in such case carbonation may occur and alter the durability of the treatment. Concerning details of the treatments, information are not available due to confidentiality reasons.…”
Section: Tested Fibers Flame Retardant Treatments and Applicationmentioning
confidence: 99%